Young Frankenstein [videorecording (DVD)] - Wilder, Gene, 1933-2016; Boyle, Peter, 1935-2006; Feldman, Marty, 1933-1982; Leachman, Cloris; Garr, Teri, 1944-; Mars, Kenneth; Kahn, Madeline; Brooks, Mel, 1926-; Shelley, Mary Wollstonecraft, 1797-1851 (20th Century Fox Home Entertainment, 2014)
Summoned by a will to his late grandfather's castle in Transylvania, young Dr. Frankenstein soon discovers the scientist's step-by-step manual explaining how to bring a corpse to life. Assisted by the hunchbacked Igor and the curvaceous Inga, he creates a monster who only wants to be loved.